Resonant vibrations of microlitre liquid drops - Temperton, Robert H. (2013)
The vibrational modes of water droplets supported on a surface (sessile drops) were excited by applying an impulse in the form of a short puff of nitrogen gas. An optical deflection technique was used to examine the modes of these oscillations in which laser light was scattered off the surface of the drops onto a photodiode. The time dependent intensity variations detected by the photodiode were Fourier transformed to give the vibrational spectra of the drops. The position and widths of the resonant peaks in these spectra were used along with a simple theory of droplet vibration to determine the surface tension and viscosity of the liquid. This theory models the resonant modes of the droplets as standing capillary wave states on the surface of a liquid bath of finite depth.